Control interno en la gestión de inventarios y su incidencia en la optimización de recursos en agrícola rancho lindo, cantón buena fé, periodo 2023. - Ipáz Vélez, Diana Carolina (2025)
Internal control represents a set of procedures and administrative policies aimed at safeguarding an organization’s resources, minimizing risks, and ensuring operational efficiency. This research aimed to evaluate internal control in inventory management and its impact on resource optimization at Agrícola Rancho Lindo, located in the canton of Buena Fé. A mixed-method approach with a field design was applied, using interviews, surveys, and direct observation, complemented by documentary and financial analysis. The results showed that the company exhibits weaknesses in process formalization, accounting valuation of inventories, and implementation of the COSO I model, which affects both efficiency and the reliability of information. The level of confidence reached was moderate (68.20%), with an identified risk of 31.80%, highlighting the need to strengthen the components related to control activities, communication, and supervision. Regarding profitability, the ROA (2.54%) and ROE (9.46%) were below optimal parameters, while the Net Profit Margin (7.02%) reflected adequate cost control. It is concluded that internal control should be strategically integrated with operational and financial management through staff training, the implementation of automated systems, and the formal adoption of the COSO model in order to achieve greater efficiency and sustainability in agricultural enterprises.